The Caenorhabditis elegans Nuclear Receptor Gene nhr-25 Regulates Epidermal Cell Development - Chen, Zhe (American Society for Microbiology, 2004)
The development of the epidermis of Caenorhabditis elegans involves cell fusion, migration, and differentiation events. To understand the mechanisms underlying these processes, we characterized the roles of NHR-25, a member of the nuclear receptor family of transcription factors. The NHR-25 homologs Ftz-F1 in Drosophila and SF-1 in mammals are involved in various biological processes, including regulation of patterning during development, reproduction, metabolism, metamorphosis, and homeostasis. Impairment of nhr-25 activity leads to severe phenotypes in embryos and many postembryonic tissues. Further analysis has indicated that nhr-25 activity is required for the proper development, including cell-cell fusion, of several epidermal cell types, such as the epidermal syncytial, seam, and Pn.p cells. Our results also suggest that nhr-25 is likely to regulate cell-cell junctions and/or fusion. In a subset of Pn.p cells, called vulval precursor cells, nhr-25 acts collaboratively with the lin-39 Hox gene in regulating vulval cell differentiation. Additionally, our data suggest that nhr-25 may also function with another Hox gene, nob-1, during embryogenesis. Overall, our results indicate that nhr-25 plays an integral role in regulating cellular processes of epidermal cells.